UNA VISIÓN HISTÓRICA SOBRE EL INSTITUTO DE LA HERENCIA (CANON DE DIBRA) - Likmeta, Engjell; Treska, Katrin (European Scientific Journal, ESJ, 2015)
In evidence of such ancient legal-civil tradition, we should pay special attention to Albanian canons. This work aims to analyze the institute of heritage in the Canon of Dibra, a canon that was applied in the region of Dibra, an ethno-cultural unit with its special tradition and culture, which consisted of nine self-governed units. These units qere governed by the regulations of the Canon of Dibra. This canon extended its effects on the central Albanian province of Dibra, which was allocated on both sides of the Black Drin River and included areas such as small and large Gryka, Bulqiza, Reci, Dardha, Çidhna, Muhurri, Luznia and Topalltia. In this article are treated the rules and provisions of the Canon of Dibra about the heritage, the circle of family members who may be heirs, the content of the right to inheritance and its basic characteristics, which are covered by a historical point of view.